Posttraumatic and Idiopathic Spike-Wave Discharges in Rats: Discrimination by Morphology and Thalamus Involvement - Ilia Komoltsev; Olga Salyp; Aleksandra Volkova; Daria Bashkatova; Natalia Shirobokova; Stepan Frankevich; Daria Shalneva; Olga Kostyunina; Olesya Chizhova; Pavel Kostrukov; Margarita Novikova; Natalia Gulyaeva (MDPI AG, 2023)
The possibility of epileptiform activity generation by the thalamocortical neuronal network after focal brain injuries, including traumatic brain injury (TBI), is actively debated. Presumably, posttraumatic spike-wave discharges (SWDs) involve a cortico-thalamocortical neuronal network. Differentiation of posttraumatic and idiopathic (i.e., spontaneously generated) SWDs is imperative for understanding posttraumatic epileptogenic mechanisms. Experiments were performed on male Sprague-Dawley rats with electrodes implanted into the somatosensory cortex and the thalamic ventral posterolateral nucleus. Local field potentials were recorded for 7 days before and 7 days after TBI (lateral fluid percussion injury, 2.5 atm). The morphology of 365 SWDs (89 idiopathic before craniotomy, and 262 posttraumatic that appeared only after TBI) and their appearance in the thalamus were analyzed. The occurrence of SWDs in the thalamus determined their spike-wave form and bilateral lateralization in the neocortex. Posttraumatic discharges were characterized by more "mature" characteristics as compared to spontaneously generated discharges: higher proportions of bilateral spreading, well-defined spike-wave form, and thalamus involvement. Based on SWD parameters, the etiology could be established with an accuracy of 75% (AUC 0.79). Our results support the hypothesis that the formation of posttraumatic SWDs involves a cortico-thalamocortical neuronal network. The results form a basis for further research of mechanisms associated with posttraumatic epileptiform activity and epileptogenesis.